Geomorphology, land use, and environmental impacts in a densely populated urban catchment of Costa Rica - Quesada Román, Adolfo (2021)
The Torres River is one of the most urbanized catchments in Costa Rica, with only 46.67 km2 and approximately 50% of its area have urban land uses comprising nearly 13% of the national population. The quick rural-urban transition during the last century has had intense environmental impacts along the Greater Metropolitan Area (GAM) of Costa Rica. We performed a geomorphology map of the Torres River catchment using photointerpretation and digitization processes. We used aerial photographs, contour lines every 5 m, digital elevation models, slope, and hillshade models as a basis. We identified eleven endogenic, fluvial accumulative and erosional, as well as anthropogenic exogenic landforms. The results show that 37% of the catchment is made up of flat lands, 31% corresponds to valley slopes, 22% to mountain slopes, and 6% to valley bottoms. The remaining 4% of the area consists of anthropogenic landforms such as deposits, terraces, quarries, escarpments, and old quarries. Land uses are controlled by the determined landforms and explain the urban growth and subsequent environmental impacts such as erosion, water pollution, and natural hazards occurrence on the catchment. This geomorphological assessment can be implemented for exhaustive morphogenetic maps, landform evolution studies, natural risks, environmental, and land use mapping.